‘Father of Honey’ empowers his community in rural Ethiopia - Tesfaye, Y.; Teshale, T.; Girma, R.; Mekuria, Wolde; Smith, J.; Hallet, P.; Phimister, E. (International Water Management Institute, 2025)
In the Great Rift Valley in Ethiopia, an intergenerational beekeeping business generates benefits for over 200 households.